Validation of an air/liquid interface device for TiO2 nanoparticle toxicity assessment on NR8383 cells: preliminary results - Leroux, Mélanie M; Doumandji, Zahra; Chezeau, Laetitia; Hocquel, Romain; Ferrari, Luc; Joubert, Olivier; Rihn, Phèdre; Rihn, Bertrand H (Cellular and Molecular Biology, 2020)
nvestigations on adverse biological effects of nanoparticles (NP) are performed usually either in vivo on rodents or in vitro under submerged conditions where NP are in suspension into cell culture media. However, sedimentation of NP in vitro is a continuous process and to assess the exact deposited cellular dose remains difficult, as the cellular internal dose is a function of time. Moreover, the cellular responses to NP under submerged culture conditions or by exposing rodents by nose-only to NP aerosols might differ from those observed at physiological settings at the air-liquid interface (ALI). Rat alveolar NR8383 macrophages were exposed to aerosols at the air-liquid interface. We studied TiO2 NM105, a mixture of anatase and rutile. NR8383 cells were exposed to a single dose of 3.0 cm2/cm2 of TiO2 aerosol. Following RNA extraction, transcriptome allowing full coverage of the rat genome was performed, and differentially expressed genes were retrieved. Their products were analyzed for functions and interaction with String DB. Only 126 genes were differentially expressed and 98 were recognized by String DB and give us the gene expression signature of exposed rat alveolar NR8383 macrophages. Among them, 13 display relationships at a high confidence level and the ten most differentially expressed compared to unexposed cells were: Chac1, Ccl4, Zfp668, Fam129b, Nab2, Txnip, Id1, Cdc42ep3, Dusp6 and Myc, ranked from the most overexpressed to the most under-expressed. Some of them were previously described as over or under-expressed in NP exposed cell systems. We validated in our laboratory an easy-to-use device and a physiological relevant paradigm for studying the effects of cell exposure to TiO2. Ccl4 gene expression seems to be a positive marker of exposure evidenced as well as in vivo or in both in vitro conditions.